Limits of the Anammox Process in Granular Systems to Remove Nitrogen at Low Temperature and Nitrogen Concentration - (:unkn) unknown (ELSEVIER, 2020)
When partial nitritation-anammox (PN-AMX) processes are applied to treat the mainstream in wastewater treatment plants (WWTPs), it is difficult to fulfil the total nitrogen (TN) quality requirements established by the European Union (<10g TN/m(3)). The operation of the anammox process was evaluated here in a continuous stirred tank reactor operated at 15 degrees C and fed with concentrations of 50 g TN/m(3) (1.30 +/- 0.23 g NO2- -N/g NH4+-N). Two different aspects were identified as crucial, limiting nitrogen removal efficiency. On the one hand, the oxygen transferred from the air in contact with the mixed liquor surface favoured the nitrite oxidation to nitrate (up to 75 %) and this nitrate, in addition to the amount produced from the anammox reaction itself, worsened the effluent quality. On the other hand, the mass transfer of ammonium and nitrite to be converted inside the anammox granules involves relatively large values of apparent affinity constants (k(NH4+app) : 0.50 g NH4+-N/m(3) ; k(NO2-app) 0.17 g NO2--N/m(3)) that favour the presence of these nitrogen compounds in the produced effluent. The careful isolation of the reactor from air seeping and the fixation of right hydraulic and solids retention times are expected to help the maintenance of stability and effluent quality. (C) 2020 Institution of Chemical Engineers. Published by Elsevier B.V. All rights reserved.